Hyalolithus didymus sp. nov. (Haptophyta): a late Miocene siliceous microfossil from Sicily, Italy. Issue 5 (3rd September 2022) - Abe, Kenta; Pellegrino, Luca; Lozar, Francesca; Tsutsui, Hideto; Jordan, Richard W.
ABSTRACT: Siliceous scales observed in an upper Miocene outcrop sample from the Caltanissetta Basin, Sicily, are similar to those of the extant haptophyte Hyalolithus neolepis and the fossil species H. tumescens . The newly discovered scales, examined by light and scanning electron microscopy, are sufficiently different to justify their assignment to H. didymus sp. nov . Like the two previously described species, the scales of H. didymus are elliptical, with a prominent marginal rim and numerous central openings (pores), separated by a submarginal hyaline area. However, the three species can be distinguished by slight (but visually recognizable) differences in the size and number of their central openings (pores). In distal view, the central area of the new species has two mounds, which are smaller and more distinct than in H. neolepis . Unlike the other two species, a swelling on the proximal side (and its corresponding depression on the distal side) has not been seen yet in H. didymus . This finding increases the knowledge of the fossil record of siliceous haptophytes, a poorly known phytoplankton group involved in the biogeochemical silicon cycle.